2002
DOI: 10.1159/000064313
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Squamous Cell Carcinoma of the Head and Neck

Abstract: Therapy for squamous cell carcinoma of head and neck relies on surgery, radiotherapy and chemotherapy, mostly a combination thereof. In patients treated with curative intent, the intensity of therapy is adapted to the supposed prognosis and should be defined upon prognostic factors. Besides classical prognostic parameters, T, N and M stage, the presence of extranodal growth (extracapsular spread, ECS), tumor volume, lymph node burden, extent of tumor necrosis, histologic grading, but also type of treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Some studies have reported patients with similar clinical prognostic features exhibiting variable responses and survival rates. 47,48 Therefore, alternate parameters that can stratify patients for optimal treatment protocol are desirable, and we believe that K trans derived from DCE-MRI can be 1 such parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported patients with similar clinical prognostic features exhibiting variable responses and survival rates. 47,48 Therefore, alternate parameters that can stratify patients for optimal treatment protocol are desirable, and we believe that K trans derived from DCE-MRI can be 1 such parameter.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide evidence for a relationship between hypoxia, as measured by 18 F-FMISO, and patient survival and are in agreement with a multitude of other cancer studies suggesting the relationship between hypoxia and patient response and prognosis. 14,15,39,52,54,[152][153][154][155] …”
Section: F-fmiso and Patient Prognosismentioning
confidence: 99%
“…While in early stages many patients can be treated in curative intention and the 5-year overall-survival is as high as 70-90%, locally advanced disease is still difficult to treat. In general, surgery (or radiotherapy, RT) is the favored treatment modality for smaller lesions (T1/T2), whereas more advanced stages (T3/T4, III/IV) are better treated with combined surgery (if possible) and RT [2]. Platinum-based concomitant chemotherapy and RT is superior to conventional RT alone in improving survival in locally advanced squamous cell carcinoma of the head and neck (SCCHN) [3].…”
Section: A New Concurrent Chemotherapy With Vinorelbine and Mitomycinmentioning
confidence: 99%